2018
DOI: 10.1017/s0016756818000481
|View full text |Cite
|
Sign up to set email alerts
|

Mercury evidence from the Sino-Korean block for Emeishan volcanism during the Capitanian mass extinction

Abstract: A prominent large negative δ13Corg excursion and a coeval notable spike in mercury (Hg)/total organic carbon ratio are observed in the middle–upper Permian Gohan Formation in central Korea, located in the eastern Sino-Korean block (SKB), which may represent the Capitanian mass extinction event. The SKB was separated from the South China block by the eastern Palaeo-Tethys Ocean. This finding from the SKB supports the widespread Hg loading to the environment emitted from the Emeishan volcanic eruptions in SW Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…25 demonstrated a volcanic trigger for the Frasnian–Famennian biotic crisis and suggested this was the Centre Hills volcanics in Central European successions. Mercury enrichments have also been described for the middle and latest Permian extinctions 18,21,26,27 . Sanei et al’s 18 study of the latest Permian mercury enrichment in the Canadian High Arctic, attributed this to emissions from the Siberian Traps with deleterious environmental consequences.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…25 demonstrated a volcanic trigger for the Frasnian–Famennian biotic crisis and suggested this was the Centre Hills volcanics in Central European successions. Mercury enrichments have also been described for the middle and latest Permian extinctions 18,21,26,27 . Sanei et al’s 18 study of the latest Permian mercury enrichment in the Canadian High Arctic, attributed this to emissions from the Siberian Traps with deleterious environmental consequences.…”
Section: Introductionmentioning
confidence: 96%
“…As has been shown recently, continental arc volcanism has a significant impact on climate change on a global scale 15 , and many studies have demonstrated that mercury anomalies are linked with large igneous provinces (LIPs) and mass extinctions 1627 , although not all LIP eruptions perturbed the Hg cycle 28 . Using Hg enrichment data, Racki et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The end-Ordovician extinction (444 Ma), end-Permian extinction (252 Ma), end-Triassic extinction (201 Ma), Toarcian OAE (183 Ma), and end-Cretaceous extinction (66 Ma), all feature Hg enrichments that can be correlated on the basis of biostratigraphic or carbon-isotope information across numerous sedimentary sequences spanning multiple regions/continents and both hemispheres (Sanei et al, 2012;Grasby et al, 2013bGrasby et al, , 2016Grasby et al, , 2017Sial et al, 2013Sial et al, , 2014Sial et al, , 2016Sial et al, , 2020Percival et al, 2015Percival et al, , 2017Percival et al, , 2018Font et al, 2016;Thibodeau et al, 2016;Gong et al, 2017;Jones et al, 2017;Fantasia et al, 2018Fantasia et al, , 2019Keller et al, 2018;Wang et al, 2018;Burger et al, 2019;Fendley et al, 2019;Lindström et al, 2019;Meyer et al, 2019;Shen et al, 2019bShen et al, , 2019cSmolarek-Lach et al, 2019;Them et al, 2019). There are also widespread stratigraphic records of the Frasnian-Famennian (372 Ma), Devonian-Carboniferous (359 Ma), and Capitanian (end-Guadalupian, 260 Ma) extinctions, the Valanginian "Weissert" Event (135 Ma), and Paleocene-Eocene Thermal Maximum (PETM, 54 Ma) that feature Hg enrichments (Grasby et al, 2016;Charbonnier et al, 2017, in press;Keller et al, 2018;Kwon et al, 2018;Racki et al, 2018aRacki et al, , 2018bJones et al, 2019;…”
Section: Do Stratigraphic Records Of All Major Events Document Hg-cycmentioning
confidence: 99%
“…Mercury enrichments across some chronological boundaries, expressed as an increase in the Hg to total organic carbon ratio (Hg/TOC), may represent true volcanogenic Hg loading to the environment (e.g., Sanei et al, 2012;Grasby et al, 2013;Percival et al, 2015;references therein). Therefore, the search for Hg/TOC spikes across major chronostratigraphic boundaries has been expanded to the whole Phanerozoic Eon (e.g., Grasby et al, 2013;Grasby et al, 2015b;Grasby et al, 2017;Grasby et al, 2019;Grasby et al, 2020;Bond and Grasby, 2017;Gong et al, 2017;Jones et al, 2017;Percival et al, 2015Percival et al, , 2017Percival et al, , 2018Burger et al, 2019;Korte et al, 2019;Shen et al, 2019aShen et al, ,b,c, 2020Sial et al, 2016;Sial et al, 2019;Sial et al, 2020a;Sial et al, 2020b;Faggetter et al, 2019;Kwon et al, 2019). Despite the growing application of Hg chemostratigraphy as a proxy for LIP activity in sedimentary successions, only a few studies have used Hg isotopes as an additional tool to demonstrate the volcanogenic origin of Hg enrichments (e.g., Sial et al, 2014;Sial et al, 2016;Sial et al, 2019;Sial et al, 2020a;Sial et al, 2020b;Thibodeau et al, 2016;Thibodeau and Bergquist, 2017;Grasby et al, 2017;Grasby et al, 2019;Gong et al, 2017;Wang et al, 2018;…”
Section: Introductionmentioning
confidence: 99%